2015
DOI: 10.1111/ajag.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caregiving status on the sleep of older New Zealanders

Abstract: Carers are at increased risk of feeling tired in the daytime. Early recognition and management of underlying sleep problems are particularly important for older people providing care at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…In contrast to a previous study which failed to find gender differences in the impact of caregiving upon sleeping problems, 50 we found significant interactions between gender and informal caring in relation to sleep disturbance, specifically similar levels of sleep disturbance in men providing no caregiving and up to 5 hours of caregiving and much higher sleep disturbance among men providing more than 5 hours of care. Women had higher levels of sleep disturbance overall; differences among women by caregiving status were smaller than among men.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to a previous study which failed to find gender differences in the impact of caregiving upon sleeping problems, 50 we found significant interactions between gender and informal caring in relation to sleep disturbance, specifically similar levels of sleep disturbance in men providing no caregiving and up to 5 hours of caregiving and much higher sleep disturbance among men providing more than 5 hours of care. Women had higher levels of sleep disturbance overall; differences among women by caregiving status were smaller than among men.…”
Section: Discussioncontrasting
confidence: 99%
“…48 , 49 Studies have shown that provision of nighttime care is associated with poorer self-reported sleep, 49 as is (albeit inconsistently) when carers and care recipients are coresident. 50–52 It might be expected that providing relatively low intensity of informal care (up to 5 hours a week) would be associated with better sleep through the mechanism of role enhancement. However, in this Swedish working sample, even low intensity caregiving was associated with self-reported sleep disturbance, suggesting that in-work carers may be experiencing stress generated by role overload in managing the competing commitments of paid work and informal caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems are among the most disruptive behavioural symptoms of dementia and have been associated with the neurophysiological pathology of the disease, exacerbated primary sleep disorders, a reduction in exposure to time cues, changes to psychosocial context as well as the impact of comorbidities and medications. Dementia-related sleep problems have been identified as exacerbating the waking symptoms of dementia (Bliwise, 2004; McCurry & Ancoli-Israel, 2003), as well as contributing to poorer sleep, reduced vitality and quality of life among family carers (Gehrman et al., 2018; Gibson, Gander, Alpass, & Stephens, 2015; Hope et al., 1998; Maun et al., 2018; McCurry et al., 2015). In a psychosocial model, sleep disturbances have been identified as a secondary stressor to those primarily related to caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…However, this finding is not consistent across all studies. For instance, Gibson et al (2015) found no significant association between care-giving status and sleep in analysis of nationally representative data of older people from New Zealand, though care-givers were significantly more likely to report feeling tired all the time. These two studies compared all care-givers to non-care-givers, however, more often particular characteristics of care-giving or the care-giver have been linked to poor sleep.…”
Section: Introductionmentioning
confidence: 99%